Superior sagittal sinus and transverse sagittal sinus thrombus secondary to occult meningioma - Bin Azeez, Anaz; Kashyap, Prashant; Dhave, Dhaval; Hakkim, Shameer; Sam Varghese, Nikhil; ., Kanishka; ., Muthukumaran (International Journal of Research in Medical Sciences, 2017)
The superior sagittal sinus is the largest of the venous sinuses. It receives blood from the frontal, parietal, and occipital superior cerebral veins and the diploic veins, which communicate with the meningeal veins. The superior sagittal sinus drains into the transverse sinuses. Central nervous system tumors like meningioma, glomus tumor, and meduloblastoma, often directly compress the veins and sinuses of the brain. Major sites of the occlusion include superior sagittal sinus (SSS) and transverse sinus. Initial days cerebral venous sinus thrombosis (CVST) was diagnosed only on autopsy. Since the advent of modern investigative modalities like magnetic resonance Imaging (MRI), Computerised Tomography Angiography (CTA) and Magnetic Resonance Venography (MRV), more and more cases are being diagnosed confidently.